2007
DOI: 10.1242/jeb.02715
|View full text |Cite
|
Sign up to set email alerts
|

Larval feeding duration affects ecdysteroid levels and nutritional reserves regulating pupal commitment in the yellow fever mosquitoAedes aegypti(Diptera: Culicidae)

Abstract: SUMMARY What little is known about the endocrine regulation of mosquito development suggests that models based on Lepidoptera and Drosophila may not apply. We report on basic parameters of larval development and the commitment to metamorphosis in the yellow fever mosquito Aedes aegypti that are affected by varying the length of feeding time for last instar larvae. A critical mass for pupal commitment was achieved after 24 h of feeding by last instars, also the age at which tissue production and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
111
0
4

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(117 citation statements)
references
References 64 publications
2
111
0
4
Order By: Relevance
“…The small-sized males and females (SMs and SFs) tested here were produced by rearing 200 newly hatched larvae with limited food supplies, whereas LMs and LFs were generated by raising 100 first instar larvae with an abundant food supply. Larvae maintained in a highly nutritious environment have more energy stores than those reared under cro wded conditions with inadequate nutrition (Telang et al, 2007). All had similar sugar feeding opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…The small-sized males and females (SMs and SFs) tested here were produced by rearing 200 newly hatched larvae with limited food supplies, whereas LMs and LFs were generated by raising 100 first instar larvae with an abundant food supply. Larvae maintained in a highly nutritious environment have more energy stores than those reared under cro wded conditions with inadequate nutrition (Telang et al, 2007). All had similar sugar feeding opportunities.…”
Section: Discussionmentioning
confidence: 99%
“…Among these species it has been variously found that commitment to moulting is triggered by abdominal stretch receptors [37], the exhaustion of a prepackaged food supply [38], or size-imposed oxygen limitation [39]. More recently it has been found that nutritional condition may better describe the process of moulting [40][41][42]. As the DEB model considers both size (structure) and nutritional condition (reserve), it offers natural handles to both of these quantities, which could be used to explore developmental triggers in insects.…”
Section: Discussionmentioning
confidence: 99%
“…Following eclosion, the water in the glass vials was removed and the glass vials along with the adult mosquitoes were stored at -20°C for 2 hours to kill the insects. Then the vials were placed in a hot air oven with a temperature of 40°C maintained for 48 hours to dry the samples, following the protocol used elsewhere (TELANG et al 2006(TELANG et al , 2007. This process was adopted for adults emerging within a 2 hour time frame; the remainder were continuously monitored for eclosion to adult stage.…”
Section: Study Sitesmentioning
confidence: 99%